#TITLE_ALTERNATIVE# - JOKO INDARTO (NIM: 13205042), ALBERTUS
A simulation of vehicular ad hoc network (VANET) is analyzed in this final project. VANET can be applied to broadcast road traffic information or Intelligent Transportation System and multimedia sharing. The scenario of this simulation is build a VANET model based on 802.11b with AODV routing protocol, grid topology model 1000 m x 1000 m and an UDP traffic generator with 1400 Byte per packet. The increased of mobile node, node’s velocity and data traffic are the vary variable of this simulation. National Chiao Tung University Network Simulator is used to simulate VANET. This software combines both traffic simulator and network simulator. Delay, packet loss, delivery packet ratio and throughput are the parameters of this simulation results. The result of VANET simulation is increasing the number of mobile node will increased the network performance, while increasing the node’s velocity will decreased the network performance.